Recent patents for detecting the species of origin in animal feedstuff, and raw and processed meat products - Rogberg Muñoz, Andres (2013)
The value of the traceability and labeling of food is attributable to two main aspects: health safety and/or product or process certification. The identification of the species related to meat production is still a major concern for economic, religious and health reasons. Many approaches and technologies have been used for species identification in animal feedstuff and food. The early methods for meat products identification include physical, anatomical, histological and chemical. Since 1970, a variety of methods were developed, these include electrophoresis (i.e. isoelectrofocusing), chromatography (i.e. HPLC), immunological techniques (i.e. ELISA), Nuclear Magnetic Resonance, Mass Spectrometry and PCR (DNA and RNA based methods). The recent patents on species detection in animal feedstuffs, raw meat and meat processed products, listed in this work, are mainly based on monoclonal antibodies and PCR, especially RT-PCR. The new developments under research are looking for more sensible, specific, less time consuming and quantitatively detection methods, which can be used in highly processed or heated treated meat food.